Alcohol and opium in the Old West use, abuse, and influence - Agnew, Jeremy 1943- (McFarland, 2014)
"This book explores the role and influence of drink and drugs (primarily opium) in the Old West, which for this book is considered to be America west of the Mississippi from the California gold rush of the 1840s to the closing of the Western Frontier in roughly 1900"--